Characterizing and Comparing Acute Responses of Blood Pressure, Heart Rate, and Forearm Blood Flow to 2 Handgrip Protocols. Issue 6 (November 2018) - Bentley, Danielle C.; Thomas, Scott G.
Abstract : Purpose: Growing evidence supports handgrip exercise training for reducing resting blood pressure (BP), with inconsistent exercise protocols reported throughout the literature. To verify safety of such protocols, real-time cardiovascular responses must be assessed. Consequently, this research sought to evaluate the acute impact of dissimilar handgrip protocols on the cardiovascular responses of BP, heart rate (HR), and forearm blood flow. Methods: Using a randomized intraindividual crossover design, 20 post-menopausal women completed 2 distinct handgrip protocols compared with a nonexercise control: 4 × 2-min sustained grips at 30% moderate intensity with 1-min rest between sets (ZONA), and 32 × 5-sec intermittent grips at maximal intensity with 5-sec rest between sets (MINT). Cardiovascular responses were measured throughout exercise and post-exercise recovery. Results: Compared to ZONA, the MINT protocol required less time and less exercise effort, yet caused greater average BP perturbations (systolic, MINT: 16.9 ± 12.9 mm Hg, ZONA: 7.9 ± 11.6 mm Hg; diastolic, MINT: 8.7 ± 7.2 mm Hg, ZONA: 4.5 ± 4.9 mm Hg) ( P < .05), with peak BP changes far below published safety guidelines. Average HR responses were similarly elevated between protocols (MINT: 5.4 ± 4.9 beats/min, ZONA: 3.4 ± 3.6 beats/min). Post-exercise recovery of BP and HR occurred swiftly following MINT while remaining elevated following ZONA. Conclusions: Handgrip exercise protocols with distinct design features (ie, grip intensity, grip strategy, and exercise duration) cause dissimilar acute cardiovascular responses. Careful and controlled attention should be directed toward determining how such acute dissimilarities influence corresponding training outcomes. Given the confirmed safety of acute BP perturbations, future researchers can have confidence in prescribing even the high-intensity MINT protocol for at-home, unsupervised activity. Abstract : To verify the safety of 2 distinct handgrip exercise protocols, real-time cardiovascular responses were assessed throughout exercise and post-exercise recovery. Although the high-intensity protocol caused greater blood pressure perturbations during exercise (as compared with a moderate-intensity protocol), peak values remained below published safety guidelines, ultimately confirming the safety of such an activity.